Pengaruh Literasi Keuangan dan Penggunaan Financial Technology terhadap Keputusan Pinjaman Online melalui Self-Control sebagai Variabel Mediasi pada Mahasiswa UGJ - Khoerunisa , Salsabila; Purdianto, Ario (Universitas Muhammadiyah Pontianak, 2026)
This study examines the influence of financial literacy and financial technology use on online loan decisions through self-control among students of the Faculty of Economics and Business, Universitas Swadaya Gunung Jati. Using a quantitative approach, data were collected from 200 students who had used online loan services and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that financial literacy and fintech use positively and significantly affect self-control and online loan decisions. Self-control also significantly mediates these relationships. These findings imply that improving financial literacy and strengthening self-control are essential to encourage more rational, responsible, and sustainable online loan decision-making among university students.